On Brazilian Helobata Bergroth, 1888 (Coleoptera: Hydrophilidae): description of two new species, new records, and key to species - Clarkson, Bruno; Santos, André Dias Dos; Ferreira-Jr, Nelson (Zootaxa, 2016)
Two new species of Helobata Bergroth, 1888 (Hydrophilidae: Acidocerinae) from Brazil are described and illustrated. Helobata amazonensis sp. nov. is described based on an adult male specimen from the Amazon River floodplains, Amazonas State. Helobata pantaneira sp. nov. is described based on an adult male specimen collected from swamps in the Pantanal biome, in Mato Grosso State. Helobata corumbaensis Fernández & Bachmann, 1987, H. larvalis (Horn, 1873) and H. quatipuru Fernández & Bachmann, 1987 are recorded for the first time from Mato Grosso; Amazonas, Ceará and Mato Grosso; and Rio de Janeiro States respectively. Diagnosis, illustrations, a checklist and a key to Brazilian species of Helobata are provided.